Photocatalyst of waste residue-based porous material doped with transition metal atoms and application thereof
Patent Information
- Application Number
- CN202610804089.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]基于此,有必要针对上述技术问题,提供废渣基多孔材料掺杂过渡金属原子的光催化剂及其应用,用于解决将废渣用作催化剂时,由于缺乏有序孔道结构和有效的异质结界面,其催化活性和稳定性难以满足实际废水处理的长效运行需求的技术问题
1、本发明提供的废渣基多孔材料掺杂过渡金属原子的光催化剂及其应用,以电子线路板行业含硅、铝、铜、锰、镍等元素的污泥或废渣为原料,经酸浸预处理、模板添加剂辅助碱熔-陈化-水热法合成高比表面积、规整孔道结构的多孔材料,实现了“以废治废”,大幅降低了催化剂的原料成本,同时减少了固体废弃物的环境风险。
Smart Images

Figure CN122875241A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalytic degradation of organic pollutants in water, and particularly to the application of photocatalysts based on waste residue porous materials doped with transition metal atoms in the degradation of organic pollutants in wastewater from the electronic circuit board industry. Background Technology
[0002] Chemical oxygen demand (COD) is a core indicator for evaluating the degree of organic pollution in water bodies. Wastewater from the electronic circuit board industry contains a large amount of recalcitrant organic pollutants, which are complex in composition, highly toxic, and have poor biodegradability, making it difficult to achieve treatment standards using traditional biological methods. Heterogeneous Fenton-like technologies have become a research hotspot for the advanced treatment of high-COD wastewater due to their advantages such as mild reaction conditions, strong oxidation capacity, and easy catalyst recovery. However, existing Fenton-like catalysts mostly use artificially synthesized molecular sieves and alumina as supports, resulting in high raw material costs and limiting their large-scale application.
[0003] The electronic circuit board industry generates large amounts of sludge or waste residue containing elements such as silicon, aluminum, copper, manganese, and nickel during production. Direct disposal not only wastes resources but also poses environmental risks. This waste residue is rich in various metals and silicon-aluminum components, making it a potential raw material for preparing porous catalytic materials. However, raw waste residue-based materials suffer from high impurity content, irregular pore structure, and poor crystallinity, making it difficult to meet the requirements of a high-efficiency catalytic carrier. To improve the structural properties of waste residue-based porous materials, researchers have explored various modification methods. Acid leaching pretreatment effectively removes soluble impurities, while adding a template agent and employing an alkali-fusion-aging-hydrothermal method can induce the formation of porous materials with high specific surface area and regular pore structure.
[0004] In existing technologies, researchers have explored various metal-supported and heterostructure construction methods to improve the catalytic efficiency of photocatalysts. For example, some studies have used simple impregnation to support transition metals, but this suffers from problems such as easy aggregation of active components and difficulty in controlling dispersion uniformity, leading to a reduction in catalytic active sites and a high recombination rate of photogenerated electron-hole pairs. Other studies have used single-metal doping, which can improve the light response to some extent, but the electron-hole pair separation efficiency remains limited, resulting in insufficient improvement in the utilization of visible light. Furthermore, when waste residue is directly used as a catalyst, the lack of ordered pore structures and effective heterojunction interfaces makes it difficult to meet the long-term operational requirements of practical wastewater treatment in terms of catalytic activity and stability.
[0005] To this end, we designed a photocatalyst based on waste residue porous material doped with transition metal atoms, which is applied to the degradation of organic pollution in wastewater from the electronic circuit board industry. We also proposed the photocatalyst based on waste residue porous material doped with transition metal atoms and its application. Summary of the Invention
[0006] Based on this, it is necessary to provide photocatalysts based on waste residue porous materials doped with transition metal atoms and their applications to address the above-mentioned technical problems. This is to solve the technical problem that when waste residue is used as a catalyst, its catalytic activity and stability are difficult to meet the long-term operation requirements of actual wastewater treatment due to the lack of ordered pore structure and effective heterojunction interface.
[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: In general, this invention uses sludge or waste residue from the electronic circuit board industry containing one or more elements from silicon, aluminum, copper, manganese, and nickel as raw materials. After acid leaching pretreatment, a high specific surface area waste residue-based porous material is synthesized using a template additive via an alkali fusion-aging-hydrothermal method. This material is then combined with two or more transition metal elements from copper, manganese, nickel, and titanium to form a heterojunction complex. This technical solution can provide a large number of highly efficient catalytic active sites, while the heterojunction effectively promotes the separation and transfer of photogenerated electron-hole pairs, significantly reducing carrier recombination, thereby significantly improving the degradation efficiency of organic pollutants in wastewater from the electronic circuit board industry, achieving "waste-to-waste treatment," and has significant environmental and economic value. Specifically, it includes: The composite photocatalyst is used in the degradation of organic pollution in wastewater from the electronic circuit board industry. The composite photocatalyst is a complex of waste residue-based porous materials doped with transition metal atoms or oxide heterojunctions.
[0008] A method for preparing a composite photocatalyst based on waste residue porous material doped with transition metal atoms, comprising the following steps: S1: Add the porous material from the waste residue to deionized water and ultrasonically treat it to form a uniform suspension of porous material based on the waste residue. S2: Add two or more transition metal salts to the waste residue-based porous material suspension obtained in step S1, stir to carry out confined adsorption, and after complete adsorption, centrifuge, wash and dry to obtain a preliminary composite photocatalyst. S3: Place the preliminary composite photocatalyst obtained in step S2 into a quartz crucible for calcination at a temperature of 100~500℃, a heating rate of 5℃ / min, and a calcination holding time of 2~12 hours to obtain a composite photocatalyst doped with transition metal atoms from the porous material based on aged waste residue.
[0009] A method for preparing a composite photocatalyst based on waste residue-based porous material doped with oxide heterojunction, comprising the following steps: A weighs 50 g of waste residue-based porous material, adds 200 mL of deionized water, and sonicates for 60 min to form a uniform suspension of waste residue-based porous material. B. The heterojunction is added to the waste residue-based porous material suspension obtained in step A, and the mixture is stirred at room temperature for confined adsorption. After complete adsorption, the mixture is centrifuged, washed, and dried to obtain a preliminary composite photocatalyst. C. The preliminary composite photocatalyst obtained in step B is placed in a quartz crucible for calcination at a temperature of 400℃, a heating rate of 3℃ / min, and a calcination holding time of 8 hours, to obtain a composite photocatalyst of oxide heterojunction doped with porous material based on aged waste residue.
[0010] A method for preparing a waste residue-based porous material includes the following steps: (1) Take the raw material waste residue into a beaker, place it on a magnetic stirrer, slowly add hydrochloric acid, stir until the solution is clear, and filter to obtain the washing waste residue; (2) Take the washing waste residue, add alkaline compound, grind to obtain a uniformly mixed mixture, transfer it to a quartz crucible; place it in a muffle furnace, heat it up, keep it at the set temperature for a set time, continue to heat it up, keep it at the set temperature for a set time, after the calcination is completed, cool it naturally to room temperature to obtain the waste residue-based porous material precursor. (3) The waste residue-based porous material precursor is placed in a hydrothermal reactor, kept at high temperature for a certain time, and then naturally cooled to room temperature to obtain the waste residue-based porous material.
[0011] Preferably, in step (1), 5-10g of raw material waste residue is placed in a beaker, placed on a magnetic stirrer, and 50-500 mL of hydrochloric acid is slowly added dropwise. The mixture is stirred for 10-30 minutes until the solution is clear, and then filtered to obtain the washing waste residue.
[0012] Preferably, in step (2), the temperature is raised from room temperature to 300~500℃ at a rate of 1~5℃ / min, held for 1~5 hours, then raised to 500-1200℃ at a rate of 2℃ / min, held for 2-12 hours, and after calcination, naturally cooled to room temperature to obtain a waste residue-based porous material precursor.
[0013] Preferably, in step (3), the waste residue-based porous material precursor is placed in a hydrothermal reactor and placed in a muffle furnace. The temperature is raised from room temperature to 50°C at a rate of 1°C / min, and the mixture is left to stand for 12 hours. The temperature is then raised to 100-150°C at a rate of 2°C / min and held for 2-12 hours. After calcination, the mixture is naturally cooled to room temperature to obtain the waste residue-based porous material.
[0014] Preferably, the raw material waste is raw material residue or sludge from the production process of an electronic circuit board manufacturer.
[0015] It is clear without a doubt that the technical solution described above in this application can solve the technical problem that this application aims to address.
[0016] Meanwhile, through the above technical solutions, the present invention has at least the following beneficial effects: 1. The photocatalyst based on waste residue and doped with transition metal atoms, provided by this invention, uses sludge or waste residue containing elements such as silicon, aluminum, copper, manganese, and nickel from the electronic circuit board industry as raw material. Through acid leaching pretreatment, template additive-assisted alkali fusion-aging-hydrothermal method, a porous material with high specific surface area and regular pore structure is synthesized, realizing "waste treatment", significantly reducing the raw material cost of the catalyst, and reducing the environmental risk of solid waste.
[0017] 2. The waste residue-based porous material prepared by this invention has a high specific surface area and abundant pore structure, which can provide a large number of efficient catalytic active sites. At the same time, through the heterojunction complex formed by loading two or more transition metal elements from copper, manganese, nickel and titanium, it effectively promotes the separation and transfer of photogenerated electron-hole pairs, greatly reduces carrier recombination, and significantly improves photocatalytic efficiency.
[0018] 3. This invention targets organic pollutants in wastewater from the electronic circuit board industry for degradation. Under simulated visible light irradiation, the removal rate of chemical oxygen demand (COD) in wastewater is significantly improved compared to traditional red mud-based or artificially synthesized molecular sieve catalysts. Through the synergistic effect of transition metal heterojunctions, the light response range is extended to the visible light region, enabling more efficient utilization of sunlight or artificial light sources. Organic pollutants can be efficiently degraded at room temperature and pressure, overcoming the shortcomings of traditional methods that require external oxidants or have high energy consumption.
[0019] 4. This invention employs a solid-phase ion exchange method or an in-situ composite method to load transition metals. The active components are highly dispersed on the carrier surface, avoiding problems such as metal agglomeration and pore blockage that are easily caused by traditional impregnation methods. It boasts high atom utilization, good catalyst stability, and excellent recyclability. Furthermore, the preparation process is relatively controllable, and the raw materials are widely available, facilitating large-scale production exploration. This provides a low-cost, high-performance technical solution for the deep treatment of high-COD wastewater from the electronic circuit board industry. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a schematic diagram of the composite photocatalyst preparation method of the present invention; Figure 2 This is a SEM image of the waste residue-based porous material of the present invention; Figure 3 This is an XRF schematic diagram of the waste residue and porous material of the present invention; Figure 4This is a schematic diagram of the infrared spectrum of the waste residue-based porous material of the present invention; Figure 5 This is a schematic diagram of BET before and after activation of the waste residue-based porous material of the present invention; Figure 6 This is an XRD diagram of the waste residue-based porous material of the present invention; Figure 7 This is a schematic diagram illustrating the phenol degradation effect of the present invention. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0023] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0024] It should be noted that, unless otherwise specified, the embodiments and features and technical solutions in the present invention can be combined with each other.
[0025] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0026] Example 1 The application of composite photocatalysts in the degradation of organic pollutants in wastewater from the electronic circuit board industry.
[0027] Specifically, the composite photocatalyst is a complex of waste-based porous materials doped with transition metal atoms or oxide heterojunctions.
[0028] When used, targeting organic pollutants in wastewater from the electronic circuit board industry for degradation, under simulated visible light irradiation, the removal rate of chemical oxygen demand (COD) in the wastewater is significantly improved compared to traditional red mud-based or artificially synthesized molecular sieve catalysts. For details, please refer to [link / reference needed]. Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 .
[0029] Specifically, this invention uses sludge or waste residue containing elements such as silicon, aluminum, copper, manganese, and nickel from the electronic circuit board industry as raw materials. Through acid leaching pretreatment, template additive-assisted alkali melting-aging-hydrothermal method, porous materials with high specific surface area and regular pore structure are synthesized, realizing "waste treatment", significantly reducing the raw material cost of catalysts, and reducing the environmental risks of solid waste.
[0030] The effect of degrading phenol is as follows Figure 7 As shown.
[0031] Example 2 refer to Figure 1 Based on the above-described Example 1, a method for preparing a composite photocatalyst doped with transition metal atoms from a waste residue-based porous material is disclosed, comprising the following steps: S1: Add the porous material from the waste residue to deionized water and ultrasonically treat it to form a uniform suspension of porous material based on the waste residue. S2: Add two or more transition metal salts to the waste residue-based porous material suspension obtained in step S1, stir at an appropriate temperature for confined adsorption, and after complete adsorption, centrifuge, wash and dry to obtain a preliminary composite photocatalyst. S3: Place the preliminary composite photocatalyst obtained in step S2 into a quartz crucible for calcination at a temperature of 100~500℃, a heating rate of 5℃ / min, and a calcination holding time of 2~12 hours to obtain a composite photocatalyst doped with transition metal atoms from the porous material based on aged waste residue.
[0032] In other embodiments, the composite assembly operation method for other transition metal atom-doped lithium slag-based porous material heterojunctions is similar.
[0033] Example 3 Based on the above Example 1, a method for preparing a composite photocatalyst using a waste residue-based porous material doped with an oxide heterojunction is disclosed, the steps of which are as follows: 1) Preparation of dispersion system: Weigh 50 g of waste residue-based porous material, add 200 mL of deionized water, and sonicate for 60 min to form a uniform suspension of waste residue-based porous material (ensure that the layers are dispersed and there is no agglomeration). 2) Addition of heterojunctions: The mass ratio of waste residue-based porous material to copper acetate, manganese acetate, and nickel acetate is 1:0.2~1:0.2~1:1:0.2~1:1 (this needs to be optimized through variable experiments; too high a ratio can easily lead to agglomeration of transition metal particles, while too low a ratio will result in weak synergistic effects). 3) Construction of heterojunction reaction: Copper acetate, manganese acetate and nickel acetate are added to the waste residue-based porous material suspension and stirred at room temperature for confined adsorption. After complete adsorption, the mixture is centrifuged, washed and dried to obtain a preliminary composite photocatalyst. The preliminary composite photocatalyst is placed in a quartz crucible for calcination at a temperature of 400℃, a heating rate of 3℃ / min and a calcination holding time of 8 hours to obtain an aged waste residue-based porous material doped with oxide heterojunction composite photocatalyst.
[0034] In other embodiments, the preparation method described in this embodiment can also be applied to the preparation process of sludge-alumina waste residue and Cu, Mn, Ni trimetallic heterojunction.
[0035] Example 4 Based on the above embodiments one to three, a method for preparing a waste residue-based porous material is disclosed, the steps of which are as follows: (1) Take 5~10g of raw material waste residue in a beaker, place it on a magnetic stirrer, slowly add 50~500 mL of hydrochloric acid, stir for 10~30 minutes until the solution is clear, and filter to obtain washing waste residue.
[0036] Preferably, hydrochloric acid is added to the waste residue at a rate of 1-2 drops / second, with continuous stirring during the addition process. After the addition is complete, stirring is continued for 30 minutes to form a homogeneous sol.
[0037] Preferably, the raw material waste residue is the raw material residue or sludge from the production process of electronic circuit board enterprises. Specifically, the raw material waste residue is sludge or raw material residue containing one or more elements such as silicon, aluminum, copper, manganese, and nickel in the electronic circuit board industry. After acid leaching pretreatment, it is used as a template additive and synthesized into waste residue-based porous materials through alkali melting-aging-hydrothermal method.
[0038] (2) Take 10-50 g of washing waste residue, add alkaline compound (calculated according to the ratio of Al:Si to alkali metal atoms 10:9-10:0.9, for example, when Al or Si is 0.02 mol, the alkali metal atoms are about 0.018-0.0018 mol), grind to obtain a uniformly mixed mixture, transfer it to a quartz crucible; place it in a muffle furnace, heat it up, hold it for a set time, continue to heat it up, hold it for a set time, after calcination, cool it naturally to room temperature to obtain a waste residue-based porous material precursor; Preferably, the dried waste obtained in step (1) is transferred to an agate mortar and ground for 12-24 hours to allow the two phases of solid to be fully mixed.
[0039] Preferably, the alkaline compound is NaOH. Grind for 0.5 to 2 hours to obtain a homogeneous mixture, and then transfer it to a quartz crucible.
[0040] Specifically, the temperature is increased from room temperature to 300-500℃ at a rate of 1-5℃ / min, held for 1-5 hours, then increased to 500-1200℃ at a rate of 2℃ / min, held for 2-12 hours, and after calcination, naturally cooled to room temperature to obtain a waste residue-based porous material precursor.
[0041] Preferably, the temperature is increased from room temperature to 450°C at a rate of 3°C / min and held for 1 hour; then the temperature is increased to 800°C at a rate of 2°C / min and held for 8 hours; after calcination, the material is naturally cooled to room temperature to obtain a waste residue-based porous material precursor.
[0042] (3) The waste residue-based porous material precursor obtained in step (2) is placed into a hydrothermal reactor, kept at high temperature for a certain time, and then naturally cooled to room temperature to obtain the waste residue-based porous material. Preferably, the waste residue-based porous material precursor obtained in step (2) is placed in a hydrothermal reactor and placed in a muffle furnace. The temperature is raised from room temperature to 50°C at a rate of 1°C / min, and the mixture is left to stand for 12 hours. The temperature is then raised to 100-150°C at a rate of 2°C / min and held for 2-12 hours. After calcination, the mixture is naturally cooled to room temperature to obtain the waste residue-based porous material.
[0043] In other embodiments, the preparation method described in this embodiment can be used in the process of preparing porous materials from sludge or other production waste.
[0044] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. The application of composite photocatalysts in the degradation of organic pollutants in wastewater from the electronic circuit board industry, characterized in that, The composite photocatalyst is a complex of waste residue-based porous materials doped with transition metal atoms or oxide heterojunctions.
2. A method for preparing a composite photocatalyst based on waste residue porous material doped with transition metal atoms, characterized in that, The steps are as follows: S1: Add the porous material from the waste residue to deionized water and ultrasonically treat it to form a uniform suspension of porous material based on the waste residue. S2: Add two or more transition metal salts to the waste residue-based porous material suspension obtained in step S1, stir to carry out confined adsorption, and after complete adsorption, centrifuge, wash and dry to obtain a preliminary composite photocatalyst. S3: Place the preliminary composite photocatalyst obtained in step S2 into a quartz crucible for calcination at a temperature of 100~500℃, a heating rate of 5℃ / min, and a calcination holding time of 2~12 hours to obtain a composite photocatalyst doped with transition metal atoms from the porous material based on aged waste residue.
3. A method for preparing a composite photocatalyst based on waste residue-based porous materials doped with oxide heterojunctions, characterized in that, The steps are as follows: A weighs 50 g of waste residue-based porous material, adds 200 mL of deionized water, and sonicates for 60 min to form a uniform suspension of waste residue-based porous material. B. The heterojunction is added to the waste residue-based porous material suspension obtained in step A, and the mixture is stirred at room temperature for confined adsorption. After complete adsorption, the mixture is centrifuged, washed, and dried to obtain a preliminary composite photocatalyst. C. The preliminary composite photocatalyst obtained in step B is placed in a quartz crucible for calcination at a temperature of 400℃, a heating rate of 3℃ / min, and a calcination holding time of 8 hours, to obtain a composite photocatalyst of oxide heterojunction doped with porous material based on aged waste residue.
4. A method for preparing a waste residue-based porous material, characterized in that, The steps are as follows: (1) Take the raw material waste residue into a beaker, place it on a magnetic stirrer, slowly add hydrochloric acid, stir until the solution is clear, and filter to obtain the washing waste residue; (2) Take the washing waste residue, add alkaline compound, grind to obtain a uniformly mixed mixture, transfer it to a quartz crucible; place it in a muffle furnace, heat it up, keep it at the set temperature for a set time, continue to heat it up, keep it at the set temperature for a set time, after the calcination is completed, cool it naturally to room temperature to obtain the waste residue-based porous material precursor. (3) The waste residue-based porous material precursor is placed in a hydrothermal reactor, kept at high temperature for a certain time, and then naturally cooled to room temperature to obtain the waste residue-based porous material.
5. The method for preparing a waste residue-based porous material according to claim 4, characterized in that, In step (1), take 5-10g of raw material waste residue in a beaker, place it on a magnetic stirrer, slowly add 50-500 mL of hydrochloric acid, stir for 10-30 minutes until the solution is clear, and filter to obtain washing waste residue.
6. The method for preparing a waste residue-based porous material according to claim 4, characterized in that, In step (2), the temperature is increased from room temperature to 300~500℃ at a rate of 1~5℃ / min, and held for 1~5 hours. Then, the temperature is increased to 500-1200℃ at a rate of 2℃ / min and held for 2-12 hours. After calcination, the temperature is naturally cooled to room temperature to obtain the waste residue-based porous material precursor.
7. The method for preparing a waste residue-based porous material according to claim 4, characterized in that, In step (3), the waste residue-based porous material precursor is placed in a hydrothermal reactor and placed in a muffle furnace. The temperature is raised from room temperature to 50°C at a rate of 1°C / min. The mixture is left to stand for 12 hours, then the temperature is raised to 100-150°C at a rate of 2°C / min. The mixture is kept at this temperature for 2-12 hours. After calcination, the mixture is naturally cooled to room temperature to obtain the waste residue-based porous material.
8. A method for preparing a waste residue-based porous material according to any one of claims 4-7, characterized in that, The raw material waste residue refers to the raw material residue or sludge from the production process of electronic circuit board enterprises.